Management of a physiotherapy department - Carol Cornell (AOSIS, 1980)
The concept of scientific management is considered. The functions of management are defined and discussed with particular reference to the management of a physiotherapy department. Qualities which are required in a supervisor are examined and the necessity for the development of management skills is stressed. The shortage of formally trained physiotherapy managers is noted and possible solutions to remedy this problem are suggested.